Sustainable governance practices for ecotourism: engaging local communities in the Golden Triangle Island, Indonesia - Tamrin, M. Husni; Lubis, Lunariana; Musleh, Moh. (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This qualitative study explores the efforts of the Sumenep District government in developing community-based ecotourism, focusing on the potential of marine tourism and small islands on Madura Island. Despite the commitment to promoting ecotourism through branding initiatives such as the tagline “Sumenep: The Soul of Madura” and the slogan “Golden Triangle Islands” highlighting Gili Iyang, Gili Labak, and Gili Genting several challenges hinder progress. These include unequal tourist distribution among the islands, inadequate infrastructure and accommodation, poor coordination in tourism management, and inefficient resource utilization. The research aims to describe and analyze governmental efforts, identify potential ecotourism types, uncover obstacles preventing optimal development, and propose a development model for community-based ecotourism. Findings indicate that significant gaps in infrastructure and management must be addressed to leverage the islands' ecotourism potential effectively. The study concludes that a comprehensive strategy, including robust regulatory frameworks, is essential to ensure sustainable and protected ecotourism in the Golden Triangle Islands, ultimately benefiting local communities and preserving natural resources.